Searching for a sustainable process of service user and health professional online discussions to facilitate the implementation of e-health. (December 2016) - Jones, Ray B; Ashurst, Emily J; Trappes-Lomax, Tessa
Many e-health projects fail to be implemented. We aimed to find a sustainable process of service user and health professional online discussions about e-health to facilitate implementation and identification of needed research. A previously piloted course compared Mental Health participants' views with publications, identifying 'quick wins' and barriers to e-health implementation. This study explored this approach further in eight domains including Health Promotion, Mental Health, and Carers. Courses comprised webinar, 1-week closed discussion forum, and final webinar. Participants discussed 12 e-health topics. Course analysis identified that five out of eight domains 'worked'. Participation was appreciated and service users influenced health professional thinking. The principle of service user–health professional online discussions to prepare for e-health implementation works for most domains, but the work of participant recruitment and forum management may make other methods, such as Tweetchats or courses hosted by existing forums where service users predominate, easier to sustain in the long term.